Uji Daya Hambat Ekstrak Daun Salam (Syzygium polyanthum wight) Terhadap Pertumbuhan Bakteri Porphyromonas Gingivalis Secara In Vitro - Monalisa Monalisa; Erly Erly; Aria Fransiska (Faculty of Dentistry Universitas Andalas, 2021)
Chronic periodontitis is the most common type of periodontitis. The main cause of chronic periodontitis is bacterial colonization of plaque. Porphyromonas gingivalis is the main pathogen and has the highest prevalence of chronic periodontitis. Bay leaf extract (Syzygium polyanthum wight) is believed to have the pharmacological effect that can be used as antibacterial. The purpose of this research was to determine the inhibitory of bay leaf extract on the growth of Porphyromonas gingivalis in vitro. The method of this research was experimental laboratories with posttest only control group design. There were 30 samples divided into 6 groups, namely bay leaf extract concentration of 2.5%, 5%, 10%, 20%, 40% and Dimethyl Sulfoxide (DMSO) as a control. Inhibitory test using the Kirby-Bauer method with a paper disc on Mueller Hinton medium agar. Inhibition zone that created around paper disc was measured with the sliding caliper. The results were analyzed with One Way Anova and Post Hoc LSD test. The results of this research showed that the mean of bay leaf extract 40% had the largest inhibition zone that was 7,6 mm and the lowest formed by bay leaf extract 2,5% that was 1,94 mm. One Way Anova test showed that there was a significant difference among the group (p<0,05). The conclusion of this research there was significant difference inhibition among 2,5%, 5%, 10%, 20%, and 40% concentration of bay leaf extract on the growth of Porphyromonas gingivalis in vitro. The higher concentration of bay leaf extract resulting the greater inhibition zone.